PENGARUH PENGUNGKAPAN INTELLECTUAL CAPITAL DAN KEPEMILIKAN INSTITUSI TERHADAP UNDERPRICING PADA PENAWARAN UMUM PERDANA - Tri Gunarsih; Wulan Handayani; Lilis Endang Wijayanti (Jurnal Ekonomi dan Bisnis, 2014)
The objective of this study is to examine the effect of intellectual capital disclosure and institutional ownership to the level of underpricing in Initial Public Offering (IPO) in Indonesian Stock Exchange. It is argued that the higher the intelectual capital disclosure the lower the level of underpricing. While because of assymmtric informatian, another argumentation is that institutional ownership influence underpricing. The sample in this study are company’s IPO in the Indonesian Stock Exchange (IDX) during 2007-2011. The sample are selected using purposive sampling method. The hypotheses are tested by running regression models. Thedependent variable is underpricing. The independent variables are the disclosure of intellectual capital and institutional ownership. This study also uses the control variable, they are return on assets, firm size, financial leverage, and underwriter reputation. The results show that intellectual capital disclosure has significant negative influence to the level of underpricing, while institutional ownership variable is not significant. Financial leverage and underwriter reputation as a control variable have significant negative effects to the level of underpricing.While other control variables are return on assets and firm size have no significant effect to the level of underpricing.Keywords: intellectual capital disclosure, institution ownership, underpricing, return on asset, firm size, financial leverage, underwriter’s reputation.